Economies of scale: A survey of the empirical literature - Karsten Junius (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1997)
If firms were animals rather than economic entities, a behavioral scientist trying to describe their traits would observe that firms tend to be found in herds and usually migrate towards the biggest watering holes. This paper surveys the literature on the questions why firms grow stronger with size, why they are found in herds, and what the effects are of meeting other herds around the watering holes. In economist-speak, I review the empirical literature on internal and external economies of scale. Internal scale economies arise on the level of a single firm. External scale economies arise on the level of an industry or a region. For each type of scale economies, I consider static and dynamic effects.
Keywords: D24; R30; 330; Economies of Scale; Empirical Studies; Skalenertrag; Industrieökonomik; Industriestandort; Agglomerationseffekt; Schätzung; Theorie; Welt